PENGARUH KEPUASAN KOMPENSASI TERHADAP KINERJA GURU DI SMP NEGERI 2 SOE - Sarce A.R. Nesimnasi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to determine the effect of compensation satisfaction on teacher performance at SMP Negeri 2 Soe. This research uses a quantitative approach with survey methods. The sample from this research was 52 teachers at SMP Negeri 2 Soe. The data collection technique is through a questionnaire distributed to all teachers at SMP Negeri 2 Soe. Data were analyzed using simple linear regression analysis. The results of the analysis show that compensation satisfaction has a significant effect on teacher performance at SMP N 2 Soe. This conclusion is drawn based on a significance level of 0.000 < 0.05, which means Ha is accepted. The regression equation formed is Y = 72.420 + 0.652X. The coefficient of determination (R Square) is 60.7%, which means that the influence of compensation satisfaction is 60.7% on teacher performance at SMP Negeri 2 Soe, while the remaining 39.3% is influenced by other factors not examined in this research. Compensation satisfaction including salary, allowances and incentives has been proven to improve teacher performance. These findings emphasize the importance of effective compensation policies to improve educational quality.